Determinants of Firm Start-Up Size and Performance of Small and Medium Enterprises (SMEs): Empirical Evidence from Uganda - Buyinza, Faisal; Mutenyo, John; Kakande, Nelson; Banga, Margret (Journal of Applied Business and Economics, 2017)
This article uses the Gender Enterprise Survey (2015), which links Ugandan SMEs start-up size and performance to business environment, entrepreneurial and enterprise characteristics. The findings indicate that entrepreneur’s education, business experience, business training, location, keeping business records, business working time and source of start-up capital are important in explaining enterprise start-up size and performance. Compared to male-owned enterprises, female-owned enterprises are consistently associated with small start-up size and lower performance. The major implication of these results is that providing business training, easing access to credit, business education and record keeping are required to promote SMEs start-up sizes and increased performance.